2022
DOI: 10.1111/sltb.12918
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of suicidal behaviors in ahigh‐risklongitudinal veteran sample: A network analysis

Abstract: Introduction: Suicide is a substantial public health burden, particularly among veterans. Risk factors have been delineated for suicide; however, the dynamic interrelations between risk factors have not been fully examined. Such research has the potential to elucidate processes that contribute to suicide risk between individuals with a past suicide attempt (attempters) and those without a past suicide attempt (nonattempters). Methods:In the current study, network analysis was used to compare networks between a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…These findings partially replicate our findings from the between-subjects network, as well as prior cross-sectional work. Specifically, several past cross-sectional network analysis studies found that perceived burdensomeness (cf., ineffectiveness) was a highly central symptom (De Beurs et al, 2019;Ortiz et al, 2023;Saulnier et al, 2023;Smith et al, 2020). Further, agitation emerged as a highly central symptom in our between-subjects model.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These findings partially replicate our findings from the between-subjects network, as well as prior cross-sectional work. Specifically, several past cross-sectional network analysis studies found that perceived burdensomeness (cf., ineffectiveness) was a highly central symptom (De Beurs et al, 2019;Ortiz et al, 2023;Saulnier et al, 2023;Smith et al, 2020). Further, agitation emerged as a highly central symptom in our between-subjects model.…”
Section: Discussionmentioning
confidence: 73%
“…Thoughts of killing oneself and feeling inadequate were central nodes for suicide networks among clinical outpatients and individuals with an eating disorder (Smith et al, 2020). Perceived burdensomeness was identified again as most central in a network analysis of a veteran sample with a history of suicide attempts (Saulnier et al, 2023). Among a sample of 50 individuals who met criteria for muscle dysmorphia, Ortiz, Grunewald, Forrest, and Smith (2023) conducted a comorbidity analysis of muscle dysmorphia and suicidal ideation symptoms and found that the most central suicide-related factor was feelings of burdensomeness.…”
mentioning
confidence: 99%
“…To our knowledge, this is the first study to utilize network analysis to examine risk factors for death by suicide among veterans. Indeed, prior work in this area has focused almost exclusively on examining risk factors for suicidal ideation and, to a lesser extent, attempts among those with and without a previous suicide attempt (Graziano et al, 2021; Saulnier et al, 2023; Simons et al, 2019). Given research to suggest that risk factors for suicidal ideation differ from those that contribute to suicidal behavior (Klonsky & May, 2015), this represents a vital step in this line of inquiry.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, to our knowledge, only a handful of studies to date have used network analysis to examine the risk for suicide among veterans. This literature has focused almost exclusively on the risk for suicidal ideation and, to a lesser extent, attempts among those with and without a previous suicide attempt (Graziano et al, 2021; Saulnier et al, 2023; Simons et al, 2019), with findings across studies generally indicating that depression exhibits a strong and positive connection to suicidal ideation. Although important, research suggests that risk factors for suicidal ideation differ from those for suicidal outcomes (Klonsky & May, 2014; Nock et al, 2016).…”
mentioning
confidence: 99%